Pengaruh Debt To Asset Ratio (DAR) dan Debt To Equity Ratio (DER) Terhadap Return On Equity (ROE) Pada Perusahaan Subsektor Transportasi Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2024 - S, Sariah; Syarif, Mahmud; Anggarini, Desy Tri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In the current digital economy landscape, more and more investors want to invest their funds in the stock market with the aim of making a profit. This study aims to determine the Effect of Debt to Asset Ratio (Dar) and Debt to Equity Ratio (Der) on Return on Equity (Roe) in Transportation Subsector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. This study uses a quantitative approach. The results of this study indicate that partially the Debt to Asset Ratio variable shows a significant positive effect on return on equity in the transportation subsector listed on the Indonesia Stock Exchange for the 2021-2024 period. Where Sig. 0.039 0.05 and t count 2.158 1.69389. The results of this study indicate that partially the Debt to Equity Ratio variable shows a significant influence on return on equity in the transportation sub-sector listed on the Indonesia Stock Exchange for the 2021-2024 period. Where Sig. 0.005 0.05 and t count -3.016 1.69389. Simultaneously, the DAR and DER variables affect the return on equity variable with a Sig value. 0.012 0.05 and f count 5.150 3.30.